Peningkatan Kemampuan Koneksi Matematik Siswa Dengan Pendekatan Kontekstual Pada Siswa - Sari, Kartika; Surya, Edi; Fauzi, Kms. Muhammad Amin (CV. Pusdikra Mitra Jaya, 2024)
The purpose of this study was to determine: 1) increasing mathematical connection abilities through a contextual approach. Educational science is a continuation of education. Education and Culture continues to carry out reforms and innovations in the field of education, one of which is curriculum renewal and innovation, namely the birth of the 2013 curriculum which is a shift in the development paradigm from the 20th century to the 21st century. Mathematics is one of the mandatory subjects in the 2013 curriculum which plays a very important role in improving human resources. Mathematical connection abilities are closely related to problem solving abilities which of course will help students to improve their mathematical connections, and vice versa. Therefore, it is very important that mathematical connection abilities to be able to improve students' mathematical connection abilities through contextual learning are a very appropriate choice. Johnson (2010:35) states that contextual learning and teaching involves students in important activities that help them relate academic lessons to the real-life contexts they face. Based on the results of research by experts, the average normalized gain score for mathematical connection abilities of students who were given contextual learning was higher than students who were given regular learning. The results of this study show that the average increase in the mathematical connection abilities of students who were given contextual learning was higher than that of students who were given regular learning.